2017
DOI: 10.1248/bpb.b16-00832
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Rich Water Attenuates Renal Injury and Fibrosis by Regulation Transforming Growth Factor-β Induced Sirt1

Abstract: The current research was designed to study the role of hydrogen in renal fibrosis and the renal epithelial to mesenchymal transition (EMT) induced by transforming growth factor-β1 (TGF-β1). Hydrogen rich water (HW) was used to treat animal and cell models. Unilateral ureteral obstruction (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Similar results were demonstrated by Zhang and colleagues in experiments on the proliferation and migration of vascular smooth muscle cells 15. Han et al showed that sirtuin (SIRT)1 is highly expressed in brain metastasis,16 and several scholars have demonstrated that hydrogen can suppress SIRT1 signaling in different models 1719. Those studies suggest that hydrogen gas has a unique therapeutic effect on the brain metastasis of NSCLC.…”
Section: Discussionsupporting
confidence: 68%
“…Similar results were demonstrated by Zhang and colleagues in experiments on the proliferation and migration of vascular smooth muscle cells 15. Han et al showed that sirtuin (SIRT)1 is highly expressed in brain metastasis,16 and several scholars have demonstrated that hydrogen can suppress SIRT1 signaling in different models 1719. Those studies suggest that hydrogen gas has a unique therapeutic effect on the brain metastasis of NSCLC.…”
Section: Discussionsupporting
confidence: 68%
“…[ 30 ] Kitamura et al [ 31 ] found that HRW protected against cisplatin‐induced nephrotoxicity and ameliorated renal dysfunction by scavenging ROS and reducing oxidative stress. Furthermore, Xing et al [ 32 ] found that HRW could inhibit the development of renal fibrosis induced by unilateral ureteral obstruction and prevent renal dysfunction. In addition, HRW treatment inhibited cell death induced by oxidative stress and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Aoki et al found that HW reduced blood lactate levels and improved exercise-induced decline of muscle function in ten male soccer players [ 47 ]. Yamazaki et al discovered that the serum 8-OHdG levels in H 2 -treated race horses were significantly suppressed, strongly suggesting a protective effect of H 2 in exercise-induced, ROS-mediated detrimental tissue damage [ 154 ]. Additionally, hydrogen bathing attenuated exercise-induced muscle damage and delayed-onset muscle soreness but had no effects on the peripheral neutrophil count and both dynamics and functions of neutrophils [ 155 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%